A lipidated form of the extracellular domain of influenza M2 protein as a self-adjuvanting vaccine candidate. Issue 30 (9th July 2015) - Zeng, Weiguang; Tan, Amabel C.L.; Horrocks, Kylie; Jackson, David C.
Highlights Lipopeptides based on the extracellular domain of influenza M2 protein constructed. Immunization of the lipopeptides protects mice against lethal viral challenge. Higher IgA and IgG2b antibodies in BAL by the i.n. immunization than the s.c. route. i.n. immunization protects mice better against viral challenge than by s.c. route. Viral challenge boosts anti-M2e antibody specificity introduced by M2e immunization.